Awareness on Eye Donation in the North-eastern State of Tripura, India – The Tripura Eye Survey. (4th July 2022) - Marmamula, Srinivas; Priya, Ruchi; Varada, Rajashekar; Keeffe, Jill E
ABSTRACT: Purpose: To determine the awareness on eye donation and willingness to pledge eyes for donation among the population aged ≥40 years in the northeastern state of Tripura, India. Methods: A population-based cross-sectional study was carried out among 2, 500 participants. The investigators conducted a detailed interview on awareness of eye donation and willingness to pledge eyes for donation. 'Awareness' was defined as having heard about eye donation. Those who reported awareness of eye donation were asked a question on willingness to pledge their eyes. Results: A total of 2, 440/2, 500 (97.6%) participants responded to the questionnaire. Among these, 1, 216 (49.8%) participants were men, and 859 (35.2%) had no education. The mean age of the participants was 54.7 years (standard deviation:12.1 years). Overall, 61.4% (95% CI:59.5–63.4; n = 1, 499) reported awareness of eye donation; of those only 3.8% (95% CI:2.9–4.9; n = 57) were willing to pledge their eyes for donation. On multivariable analyses, the odds of awareness were higher among those who had school education (OR:2.12; 95% CI: 1.73–2.56) or higher education (OR:11.79; 95% CI:7.35–18.93). Deformity associated with eye donation (n = 327;76.9%) followed by religious reasons (n = 63; 14.8%) and a belief that those who donate eye are 'born blind in the next birth' (n = 23; 5.4%) were the main reasons for lack of willingness to pledge their eyes for donation. Conclusions: Although the awareness regarding eye donation was satisfactory, there was lack of willingness to pledge eyes for donation. There is a need for focussed information, education, and communication campaigns to encourage eye donation in Tripura.